2023
DOI: 10.3390/bs13100839
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Problematic Smartphone Use, Sleep Quality and Bedtime Procrastination: A Mediation Analysis

Santiago Correa-Iriarte,
Sergio Hidalgo-Fuentes,
Manuel Martí-Vilar

Abstract: The purpose of this investigation was to study the relationship between sleep quality, problematic smartphone use (PSU) and bedtime procrastination, as well as to assess gender and age differences. A total of 313 participants, aged 18–60 (M = 30 ± 10.1; 53.2% males), completed an online survey between February and May 2023 in Spain. The Pittsburgh Sleep Quality Index, Smartphone Addiction Scale-Short Version and Bedtime Procrastination Scale were used to measure sleep quality, PSU and bedtime procrastination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 138 publications
0
0
0
Order By: Relevance
“… 44 , 45 This study confirms that bedtime procrastination plays a mediating role, as previous literature has shown a connection between bedtime procrastination and low sleep quality. 23 , 25 , 46 The literature explains bedtime procrastination associated with PSU with the nature of phone applications designed to keep users for a long time, losing time awareness while using the smartphone and taking time for oneself by using the smartphone after a busy day, smartphone use affects circadian rhythm and increased arousal pathways before sleep. 14 , 15 , 19 , 47 The indirect effects of bedtime procrastination behavior, a less explored topic in adolescents than adults, could guide future research examining mediating variables influencing sleep quality in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 , 45 This study confirms that bedtime procrastination plays a mediating role, as previous literature has shown a connection between bedtime procrastination and low sleep quality. 23 , 25 , 46 The literature explains bedtime procrastination associated with PSU with the nature of phone applications designed to keep users for a long time, losing time awareness while using the smartphone and taking time for oneself by using the smartphone after a busy day, smartphone use affects circadian rhythm and increased arousal pathways before sleep. 14 , 15 , 19 , 47 The indirect effects of bedtime procrastination behavior, a less explored topic in adolescents than adults, could guide future research examining mediating variables influencing sleep quality in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite studies examining the mediating effect of variables such as self-regulation, bedtime procrastination, and fear of missing out on sleep quality on the effect of smartphone use in the adult age group, there are not enough studies in adolescence, which is a critical period for mental and physical development. 23 - 25 This study aimed to learn the frequency of smartphone use and types of activities in bed before sleep, the relationships, and sex differences between PSU, bedtime procrastination, and sleep quality in Turkish adolescents. In addition, the mediating effect of bedtime procrastination between PSU and sleep quality was also examined.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that phubbing behavior, which involves snubbing someone in a social setting by focusing on one's phone rather than engaging in direct conversation with the person present, can have a detrimental impact on individuals' relationships with their significant others ( Chotpitayasunondh & Douglas, 2018 ; Roberts & David, 2016 ). Higher levels of problematic mobile phone use are associated with greater levels of sleep interference (procrastination in bedtime scheduling), leading to more significant sleep disorders (e.g., Correa-Iriarte, Hidalgo-Fuentes, & Martí-Vilar, 2023 ; Cui et al., 2021 ; Hamvai et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%